Prestasi Kerja Karyawan Dipengaruhi Penilaian Kinerja, Pengawasan, Dan Lingkungan Kerja Non Fisik PT Pos Kediri - Pratama, Christanova Andika; Munir, Miftahul; Ayuanti, Rafikhein Novia (Universitas Maritim AMNI Semarang, 2025)
This study aims to analyze the influence of performance appraisal, supervision, and non-physical work environment on employee performance at PT Pos Indonesia (Persero) Kediri Branch Office. A quantitative approach was employed with saturated sampling, in which all 64 employees were included as respondents. The research instrument was a questionnaire based on validated theoretical and empirical indicators. Data were analyzed using multiple linear regression, t-test, F-test, and the coefficient of determination. The findings indicate that, partially, performance appraisal, supervision, and non-physical work environment have a positive and significant effect on employee performance. Simultaneously, these three variables contribute 70% to the variation in employee performance, with the non-physical work environment being the most dominant factor. These results highlight the importance of integrating transparent performance appraisal systems, consistent supervision, and a supportive organizational climate to improve employee productivity. This research contributes academically by reinforcing the Goal Setting theory and Perceived Organizational Support, and provides practical implications for PT Pos Indonesia’s human resource management.